Limites e possibilidades dos processos de reestruturação e implantação curricular: a experiência de um curso de pedagogia no estado da Bahia - Guedes, Marilde Queiroz (2010)
This thesis has as its central theme the curricular restructuring and implantation process of the course of Pedagogy. It had as its locus a public multicampi institution in the Brazilian State of Bahia, the Universidade do Estado da Bahia (UNEB). The national curricular guidelines for the course of Pedagogy were instituted by means of the Resolution 2006/1 of the Education National Council (CNE), a legal regulation which carried out changes on the course, producing exigencies to the institutions of Higher Education in order to promote curricular reformations which would make them adequate to the instituted. In this investigation, the aim was to analyze how students, professors and managers have understood the curricular restructuring and implantation process. To achieve it, was followed the methodological way of qualitative research (LAVILLE; DIONNE, 1999; LÜDKE; ANDRÉ, 1986; GAMBOA, 2007) aiming to interpret and to reveal, from an ethic and critical-reflexive view, the contradictions and complexities of the object under investigation. The adopted instruments for the data construction consist in content analysis (BARDIN, 1995), questionnaires, interview, focal group and researcher s direct observation. The founts triangulation, with basis on Bogdan and Bilken (1994) was used. The data analysis had as its reference the legal framework which rules the course of Pedagogy, as follows: the over mentioned Resolution and other Documents of the CNE Basic Education Chamber, especially n. 2005/5 and n. 2006/3 as well as theoretical contributions of authors of the areas of Curriculum, Pedagogy and Formation of Teachers. The research has revealed, among other evidences, that the curriculum restructuring and implantation process has been understood as difficult, conflicting, marked by power relationships, although at the same time by negotiations and consensus which made it possible to organize and to elaborate a new curriculum consonant with the determinations engraved in the guidelines. The data point out too that, in managers conceptions, the curricular restructuring has weakened because of the agents fragmentation during curriculum elaboration, because of the least participation of the Campi, and because of the lack of a diagnosis which could offer subsidies to the methodology and to the content of the new curricular organization. Still according to the data, the protagonists are seriously upset about the new curriculum implementation